Study on the Interchangeability Condition of the Tooth Matching Method of RV Reducer - Gao Wenming; Gong Linhuan (Jixie chuandong)
The assembly conditions of 2K- H planetary transmission is analyzed,and the conclusion that the first planetary transmission in RV reducer don’’t need to meet the assembly conditions is put forward. On the basis of considering the manufacture technics and interchangeability,the interchangeability conditions are put forward. The tooth matching method of RV reducer under the interchangeability condition is introduced and used to design the toothed parameters of RV- 80- 120 RV reducer. The results show the correctness and effectiveness of this method.